ナンキョク ロケット ニヨル プラズマ ハドウ ジッケン ノ モンダイテン ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 松本, 紘; マツモト, ヒロシ; 木村, 磐根; キムラ, イワネ; MATSUMOTO, Hiroshi; KIMURA, Iwane (国立極地研究所, 1972)
P(論文) As a part of the proceedings of "Symposium on future planning of rocket observation at Antarctica", problems of the rocket experiments on plasma wave phenomena are briefly discussed. Engineering requirements for the rocket experiments of the wave phenomena in the future are first described and then scientific missions of plasma wave observations and experiments at Antarctica are discussed. departmental bulletin paper